Lysosomal membrane integrity in fibroblasts derived from patients with Gaucher disease - Asuka Hamamoto; Natsuki Kita; Siddabasave Gowda B. Gowda; Hiroyuki Takatsu; Kazuhisa Nakayama; Makoto Arita; Shu-Ping Hui; Hye-Won Shin (Cell Structure and Function, 2023)
Gaucher disease (GD) is a recessively inherited lysosomal storage disorder characterized by a deficiency of lysosomal glucocerebrosidase (GBA1). This deficiency results in the accumulation of its substrate, glucosylceramide (GlcCer), within lysosomes. Here, we investigated lysosomal abnormalities in fibroblasts derived from patients with GD. It is noteworthy that the cellular distribution of lysosomes and lysosomal proteolytic activity remained largely unaffected in GD fibroblasts. However, we found that lysosomal membranes of GD fibroblasts were susceptible to damage when exposed to a lysosomotropic agent. Moreover, the susceptibility of lysosomal membranes to a lysosomotropic agent could be partly restored by exogenous expression of wild-type GBA1. Here, we report that the lysosomal membrane integrity is altered in GD fibroblasts, but lysosomal distribution and proteolytic activity is not significantly altered. Key words: glucosylceramide, lysosome, Gaucher disease, lysosomotropic agent